Evaluation of Malaysian primary English language textbooks - Md Sungif, Nur Atiqah; Abang Ahmad, Dayang Hartijah; Mukundan, Jayakaran (Australian International Academic Centre, 2014)
The purpose of this study is to evaluate the contents of in-use Year 5 and Year 6 textbooks in Malaysian primary schools in exploring the strengths and weaknesses of the textbooks. Does it really apply all the methods and suitability for the pupils? It is also aim to study whether the textbooks fit to all level of pupils’ proficiency in English language and whether it giving attention on the pupils’ proficiency level in language learning. Sample of the study consists of 32 English teachers chosen randomly from primary schools in Selangor. In this study, the textbook is evaluated in terms of general attributes and learning content categories and evaluation checklists proposed by previous researchers are distributed as instrument used. The findings revealed that the textbook for each year is very highly useful. It is also found that the textbooks are suitable for either for low proficiency or vice versa.